Unveiling the arsenal against antibiotic resistance: Antibacterial peptides as broad-spectrum weapons targeting multidrug-resistant bacteria - Ibrahim Mohammed Hussaini; Asmau Nna Sulaiman; Salim Charanchi Abubakar; Tariq Mohammed Abdulazeez; Murjanatu Muhammad Abdullahi; Mamunu Abdulkadir Sulaiman; Abubakar Madika; Musa Bishir; Aliyu Muhammad (The Microbe)
The emergence of antibiotic resistant bacteria is a serious challenge of public health concern. The increasing concern of antibiotic resistance has necessitated the need for alternative therapeutic options. Antibacterial peptides are broad-spectrum bactericidal compounds with promising activity against multidrug resistant bacteria, hence their recognition as an emerging therapeutic approach against multidrug resistant bacteria. Naturally occurring antibacterial peptides are mostly sourced from plants, amphibians, mammals, insects, and microorganisms. Aside from naturally occurring antibacterial peptides, many synthetic peptides have also been produced. Most peptides exhibit antibacterial activity by physically disrupting the cell membranes of bacteria, while other peptides target non-membrane structures such as bacterial cell walls and intracellular components of the bacteria. This review highlights the antibacterial activity of antibacterial peptides against bacteria including drug-resistant bacterial strains. Some of these peptides exhibited antibacterial activity when used alone while others exhibited synergistic antibacterial activity when used with antibiotics. The review also outlines the mechanism of antibacterial peptide resistance among bacteria and various techniques used for the chemical modification of peptides to enhance their bioactivity and stability. Existing antimicrobial peptide databases were also summarized in this review. This review gives an insight into the therapeutic use of antibacterial peptides as an alternative therapeutic option for the treatment of infection caused by antibiotic resistant bacterial strains.